Magnetic Anisotropy of the Westboro Formation in the Middlesex Fells Reservation, Stoneham, Ma: the Style of Deformation of a Small Piece of Avalon. - Lowe, Katherine E. (Tufts Archival Research Center, 2014)
Abstract: The Westboro Formation in eastern Massachusetts is a metasedimentary rock unit of Proterozoic age that makes up part of the Avalon Terrane. Anisotropy of magnetic susceptibility was used to study tectonic deformation of the formation. Supporting previous work by Bailey et al. (1984), limited deformation was found in the form of shearing along bedding. Overall, the deformation was weak with low strain, though the degree of deformation varied throughout the study area. At two sites laminated bedding was well preserved and there was an original sedimentary magnetic fabric. This fabric had its maximum susceptibility at a low angle to the nearly vertical bedding plane, suggesting a sedimentary imbrication. All other sites with a structural foliation showed some degree of sedimentary magnetic fabric reorientation as a result of tectonic deformation. These sites show maximum susceptibilities of samples spread on the structural foliation plane. One site experienced greater deformation than others and the original sedimentary fabric is completely reoriented with maximum susceptibilities clustering as a weak lineation at ENE with a shallow plunge. Magnetic fabrics are consistent with bedding and foliation features seen in the field and can be used as a tool for structural analysis in locations where bedding or foliation cannot be clearly measured at an outcrop scale.